The Effect of Functional Electrical Stimulation on Balance Function and Balance Confidence in Community-Dwelling Individuals with Stroke - Robertson, Jennifer A. (University of Toronto Press Incorporated, 2010)
Purpose: The purpose of this study was to evaluate the change in balance function and balance confidence in adults with chronic stroke who are starting a gait re-education program with functional electrical stimulation (FES). Methods: The study used a before–after study design. Fifteen community-dwelling adults with chronic stroke completed four weekly sessions (2 hours each) of balance and ambulation training with FES applied to the ankle dorsiflexors during the swing phase. Following this familiarization period, participants were assessed for balance and mobility with and without the use of FES. Balance confidence was assessed before and after the familiarization period using the Activities-specific Balance Confidence (ABC) scale. Results: There was a small but statistically significant improvement in toe clearance and balance function with the FES device, but no detectable change in gait speed. More than half of participants reported reduced balance confidence with the FES device; one-third showed a large (>11 ABC points) reduction in balance confidence. Conclusion: Physical improvements can occur during FES treatment of individuals post-stroke; however, this may be associated with a clinically important impairment in balance confidence as patients with stroke familiarize themselves with FES treatment.